My Little Gentleman - Roth, Maddy (Cornfield Review, 2017)
Honestly, this was written on the spot but once it stared coming I just couldn't stop it. It has a lot of raw emotion in it, and theres a good chance I'll cry again if we go over it as a class but I want to contribute.